Genetic engineering of Ehrlich pathway modulates production of higher alcohols in engineered Yarrowia lipolytica. Issue 2 (18th November 2018) - Celińska, Ewelina; Borkowska, Monika; Białas, Wojciech; Kubiak, Monika; Korpys, Paulina; Archacka, Marta; Ledesma-Amaro, Rodrigo; Nicaud, Jean-Marc
Abstract: Microbial cells can produce a vast spectrum of chemical compounds, including those most desired by the global chemical market, for example, higher alcohols, which are promising alternative fuels and chemical feedstock. In the current research, we investigated the effects of the Ehrlich pathway genetic engineering on higher alcohols production in Yarrowia lipolytica, which directly follows our previous findings concerning elucidation of putative molecular identities involved in this pathway. To this end, we constructed two alternative expression cassettes composed of previously identified genes, putatively involved in the Ehrlich pathway in Y. lipolytica, and cloned them under the control of constitutive pTEF promoter, and by this released them from extensive native regulation. The effects of the pathway engineering were investigated upon provision of different Ehrlich pathway-inducing amino acids (L-Phe, L-Leu, L-Ile and L-Val). In general, amplification of the Ehrlich pathway in many cases led to increased formation of a respective higher alcohol from its precursor. We observed interesting effects of aminotransferase BAT2 deletion on synthesis of 2-phenylethanol and its acetate ester, significant relationship between L-Val and L-Phe catabolic pathways and extensive 'cross-induction' of the derivative compounds synthesis by non-direct precursors. Abstract : Amplification or deletion of Ehrlich pathway components modulate production of valuable chemicals in Yarrowia lipolytica strains cultured with different Ehrlich pathway-inducing amino acids.